Analysis of Crashworthiness of Bishoftu Pickup Vehicle Structure during Side Pole Crash - Adane Gashu; Ramesh Babu Nallamothu (Journal of Engineering)
Now a day’s, vehicle accident is becoming a critical issue all over the world, especially in Ethiopia. These vehicles have not been checked for any crash safety test specifications and are not evaluated for crashworthiness. So, it is now time to consider the safety features of Bishoftu pickup vehicles (BPV) to reduce the grave consequences for their users. This paper aimed to improve the crashworthiness of the existing Bishoftu pickup vehicle through remodeling. The structural response to a frontal collision with an existing BPV is analyzed. Based on the results obtained from the existing model, modifications are made by means of energy-absorbing components, a stable frame structure, and better crash performance. For doing the analysis software like CATIA is used for 3D modeling, and LS-DYNA is used for FEM analysis. The results show that by applying the modification, 39 kN (7.82%) of impact force is reduced and 5 kJ (3.52%) of additional energy is absorbed during the frontal collision. Finally, it can be concluded that with the modified model, the safety and crashworthiness of the BPV were greatly improved without affecting the appearance and weight of the existing one.